Preparation of Palladium Supported on Ferric Oxide Nano-catalysts for Carbon Monoxide Oxidation in Low Temperature - Wang, Fagen; Xu, Yan; Zhao, Kunfeng; He, Dannong (Nano-Micro Letters, 2014)
Catalytic property of Pd/Fe2O3 catalysts on carbon monoxide (CO) oxidation at low temperature were investigated in this paper. Both the as-prepared and H2-pretreated Pd/Fe2O3 catalysts show catalytic performances on CO oxidation. The CO was completely converted at 333 K for the as-prepared sample, whereas at 313 K for H2-pretreated Pd/Fe2O3-573 catalyst. The catalytic performance of the Pd/Fe2O3 catalyst decreases with increased calcination temperature. This may be due to the increased crystallinity of the support and decreased metal-support interaction. Progressive deactivation of the catalysts during long-time reaction was associated with the formation of carbonates on the catalyst surface that inhibits CO activation or intermediate transformation.